Justiciability of Economic, Social and Cultural Rights: The Case of the Right to Water under Argentine Jurisprudence - Cenicacelaya, María de las Nieves (DIXI, 2015)
Purpose: Ths article reports on how Argentine courts have been recognizing access to water as a fundamental right, applying the most signifiant international standards in that fild. Description: Based on the premise that human rights are universal, indivisible and interdependent, and that placing them in a supposed hierarchy is inadmissible. In effct, the Argentine courts discard the idea that economic, social and cultural rights, compared to civil and political rights, could be in a second-class category. On the contrary, because these are rights whose enforcement can absolutely be demanded, at least in their essential levels, states, until they progressively reach the highest possible level, have, among other duties, the obligation to fulfil them, which includes access to the courts to guarantee their effctiveness. Point of view: In this sense, the article primarily focuses on the right of all human beings to have safe water for personal and domestic use, postulating its full enforceability and justiciability. Conclusions: Aftr a review of its internal and international legal and regulatory recognition, the article shows how some of the most valuable rulings by Argentine courts have gradually strengthened the human right to water.